An Analysis of Islamic Education Values in Serat Wedhatama by Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A) Mangkunegara - Rahman Afandi; Adie Setiawan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This article explores the Islamic educational values embedded in Serat Wedhatama, a classical Javanese literary work authored by Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A) Mangkunegara, recognized for its profound religious and moral teachings. The study aims to uncover the Islamic values conveyed through the text and assess their relevance to education character in the contemporary era. Employing a descriptive qualitative method with a philological approach and content analysis, data were collected through an in-depth literature review of the Serat Wedhatama manuscript and related scholarly works. The findings reveal that the text embodies key Islamic educational values, including tauhid (the oneness of God), akhlak (morality), tasawuf (spiritual purification), and the pursuit of knowledge. These values are articulated through themes of self-awareness as a servant of God, the control of human desires, and the attainment of spiritual happiness. The study highlights that Serat Wedhatama transcends its literary form, functioning as a medium of Islamic moral education deeply rooted in Javanese cultural identity. The integration of its values into modern character education curricula holds significant potential for shaping individuals who are spiritually grounded, intellectually equipped, and morally upright. In conclusion, Serat Wedhatama represents a rich source of local wisdom that continues to offer relevant and transformative insights for Islamic education in the modern educational landscape.